KEPEMIMPINAN DAN MANAJEMEN PENDIDIKAN ISLAM - Ansori; Repolinda; Jamilah; Kasful Anwar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This article explores in depth the strategic role of leadership and management in Islamic educational institutions. Islamic education does not merely aim to develop students intellectually, but also seeks to instill spiritual, moral, and social values. Therefore, the success of Islamic educational institutions is highly influenced by leaders who can serve as role models (uswah hasanah), possess strong managerial competencies, and uphold Islamic values such as trustworthiness (amanah), justice (‘adl), and deliberation (musyawarah). The research method employed is library research with a descriptive-analytical approach, reviewing relevant literature including scholarly books, journals, and classical and contemporary Islamic sources. The findings reveal that leadership and management grounded in Islamic values impact not only academic achievement but also significantly contribute to character building and the organizational culture of educational institutions. The implementation of prophetic leadership values and systematic management based on sharia emerges as a solution for building excellent Islamic education—responsive to contemporary developments while preserving the spiritual essence of Islam.